The Dilemma of Identity Politics Strategy - Yohanes Orong (Asian Journal of Philosophy and Religion, 2024)
This article aims to critically highlight the affirmation of identity politics narratives in Indonesia. For this purpose, the text of Ummat Party Chairman Ridho Rahmadi's political speech is used as the object of attention. Points of critical analysis of the New Social Movement (NSM) theory of identity politics are used to highlight Ridho Rahmadi's political speech. Collective identity, including identity politics, is necessary to mobilize social movements. In this case, the expression of identity is used as a political strategy, so that in the end the collective identity can become the goal of social movement activism. However, in the context of the Unitary State of the Republic of Indonesia, which is multicultural, multiethnic, multiracial, and multi-religious, does the presence of a political party that clearly excludes itself as a party with Islamic identity by making the mosque a node of political jihad, not threaten national unity? From the perspective of NSM theory, social movement mobilization can indeed be triggered by collective identity-based political movements such as those launched by the Ummat Party. However, the same theory also emphasizes the strategic dilemma of such social movement mobilization, namely that the identity that is the basis for organizing a movement is also the basis for oppression, persecution and exploitation.